Joint surgery rates in lupus: a long-term cohort study - Helen Isobel Keen; David Brian Preen; Johannes Nossent; Charles A Inderjeeth (Lupus Science and Medicine)
Aim With scarce data on the need and type of joint surgery in SLE, we investigated the long-term rates and underlying causes for arthroplasty, arthrodesis and synovectomy in patients with SLE.Methods Procedure dates for arthroplasty, arthrodesis or synovectomy were retrieved from the state-wide Hospital Morbidity Data Collection between 1985 and 2015 for patients with SLE (n=1855) and propensity-matched controls (n=12 840). Patients with SLE with ≥two additional diagnostic codes for rheumatoid arthritis were classified as rhupus. ORs and incidence rates (IRs) per 100 person-years for joint procedures (JPs) were compared among patients with rhupus, patients with other SLE and controls across three study decades by regression analysis.Results More patients with SLE than controls underwent a JP (11.6% vs 1.3%; OR 10.8, CI 8.86 to 13.24) with a higher IR for JP in patients with SLE (1.9 vs 0.1, rate ratio 19.9, CI 16.83 to 23.55). Among patients with SLE, patients with rhupus (n=120, 60.5%) had the highest odds of arthroplasty (OR 4.49, CI 2.87 to 6.92), arthrodesis (OR 6.64, CI 3.28 to 12.97) and synovectomy (OR 9.02,CI 4.32 to 18.23). Over time, the IR for overall JP in patients with rhupus was unchanged (8.7 to 8.6, R2=0.004, p=0.98), although the IR for avascular necrosis underlying arthroplasty decreased for all patients with SLE (0.52 to 0.10, p=0.02). Patients with other SLE also had significantly higher OR and IR for all three JPs than controls with insignificant decreases in synovectomy and increases in arthroplasty over time in this group.Conclusions The overall burden of joint surgery in SLE is high and despite a reduction in avascular necrosis, arthroplasty and arthrodesis rates have not decreased over time. These data indicate a need for increased efforts to prevent joint damage in patients with lupus.